The Effectiveness of Integrated Chemistry Teaching Materials Islamic Values and Local Wisdom Sasak Towards Science Process Skills and Social Concern on the Chemical Bonding Material - Aldian, Hendy; Wahyudiati, Dwi (Tauladan Fathimah Azzahra, 2024)
This research aims to: (1) know the effectiveness of integrated chemical teaching materials of Islamic values and Sasak local wisdom on science process skills and social concern in chemical bonding materials; and (2) understand the differences in science process skills and students’ social care through the application of integrated chemistry teaching materials Islamic values and Sasak local wisdom to chemical bond materials. The research method used is experimental research with a quantitative approach. The experimental class was given treatment with integrated chemistry teaching materials of Islamic values and Sasak local wisdom, and the control class was given treatment with conventional chemistry teaching materials. Data analysis techniques using Hotelling’s T2 hypothesis test through the Manova test. Based on data analysis using the Manova test, obtaining integrated chemistry teaching materials for Islamic values and local wisdom Sasak is effective on science process skills and social care with a significance value of 0.000 < 0.05 based on the results of the Manova test Test of Between-Subject Effect and Hotteling’s T2 test. In addition, it refers to the Partial Eta Squared value where the score for science process skills is 0.414 and social care is 0.688. It can be seen that the value of Partial Eta Squared for social care is greater than that of science process skills, so the bound variable that is most influenced by the integrated chemical teaching materials of Sasak Islamic values and local wisdom is the variable of social concern.